2018
DOI: 10.1070/rcr4837
|View full text |Cite
|
Sign up to set email alerts
|

Adducts of transition metal complexes with redox-active ligands: the structure and spin-state-switching rearrangements

Abstract: The currently available literature data on the synthesis, molecular and electronic structure of mixed-ligand complexes (adducts) of transition metals (chromium, manganese, iron, cobalt, ruthenium) with organic redox-active ligands are systematically considered for the first time. The possibility of manifestation of magnetic bistability by adducts of tetracoordinate CoII and FeII complexes and the potential for their application as molecular switches are studied in detail by means of quantum chemical modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 164 publications
0
26
0
Order By: Relevance
“…Based on the experimental data and earlier performed theoretical investigations, one can assume that the most interesting magnetic properties would be manifested by the dinuclear systems IV , in which diimine fragment of the tetradentate ligand is coordinated to the cobalt ion, while phenanthroline (phen) moiety is bound with the iron center. Such type complexes are potentially capable of occurrence of the VT Co II /Co III and SCO LS Fe II / HS Fe II rearrangements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the experimental data and earlier performed theoretical investigations, one can assume that the most interesting magnetic properties would be manifested by the dinuclear systems IV , in which diimine fragment of the tetradentate ligand is coordinated to the cobalt ion, while phenanthroline (phen) moiety is bound with the iron center. Such type complexes are potentially capable of occurrence of the VT Co II /Co III and SCO LS Fe II / HS Fe II rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Diimine fragment of this ligand is suitable for the construction of VT systems with cobalt bis‐chelates . It might be expected that directional variation of the metal centers could lead to dinuclear compounds, spin states of which are controlled by the two mentioned above mechanisms (SCO and/or VT).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the incoming electron preferentially enters or is trapped into an energetically low‐lying stabilized ligand‐based delocalised orbital. Whilst this has been well‐documented for transition metal systems, only a few actinide systems have been reported …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the incoming electron preferentially enters or is trapped into an energetically lowlying stabilized ligand-based delocalised orbital. Whilst this has been well-documented for transition metal systems, [12][13][14][15][16] only a few actinide systems have been reported. [7,9,[17][18][19][20][21][22] For example, whilst examining the VI to V reduction potentials of actinyl ([AnO 2 ] 2 + ; An=U, Np and Pu) alaskaphyrin complexes, Shamov et al [9] identified ligand reduced species for the one-electron reduction of a [U VI O 2 -alaskaphyrin] complex rather than the anticipated [U V O 2 -alaskaphyrin]species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation